Systematic inflammatory indicators and clinical management of exogenous endophthalmitis due to metal penetrating injury of eyeball - Wu, Donghai; Lin, Yuan; Wu, Huping; Cai, Jinhong (Frontiers in Medicine, 2024)
Objective: To evaluate systemic inflammatory markers in cases of exogenous endophthalmitis caused by metal foreign bodies after penetrating eye injury and identify risk factors for poor control post-initial emergency surgery.Methods: Twenty-nine patients with exogenous endophthalmitis underwent emergency surgery with vitrectomy at Xiamen Eye Center (2016-2024). Evaluations included systemic inflammatory markers, microbiology, clinical presentation, treatment strategies, complications, prognostic factors, and visual outcomes.Correlation analysis was performed between blood test results and disease control after initial surgery.The median patient age was 44.8 ± 16.9 years, with an average treatment delay of 6.1 ± 10.6 days. Males represented 86.2% (n=25), and 41.3% (n=12) had metallic intraocular foreign bodies, which correlated with faster symptom onset (p < 0.05) and higher inflammatory markers (WBC, neutrophils, basophils, CRP; p < 0.05).Primary lens extraction and intraoperative vancomycin did not significantly improve control (p > 0.05). Poor control post-vitrectomy was positively correlated with intraocular foreign bodies (R = 0.39, P < 0.05) and negatively with lymphocyte and monocyte counts (R = -0.43, P < 0.05; R = -0.46, P < 0.05). Early intervention within 2 hours of symptom exacerbation reduced complication risk (AUC = 0.708, 95% CI: 0.547-0.838, P = 0.047).Metallic intraocular foreign bodies provoke stronger systemic inflammatory responses, posing control challenges, especially in patients with lower immune resilience. Timely vitrectomy during initial emergency surgery is crucial for managing endophthalmitis.